Pathological changes in red tilapias (Oreochromis spp.) naturally infected by Streptococcus agalactiae - Saad, Mohd Zamri; M. N. A., Amal; Abdullah, Siti Zahrah (Elsevier Ltd, 2010)
The pathological changes present in 300 red tilapias (Oreochromis spp.) naturally infected by Streptococcus agalactiae are described. The most consistent gross findings were marked congestion of internal organs, particularly the liver, spleen and kidneys. Other features included exophthalmos, softening of the brain and the occasional accumulation of fluid within the abdominal cavity. Microscopical examination confirmed the presence of marked congestion of the liver, spleen and kidneys. The endothelial cells lining major blood vessels of the liver and occasionally the spleen were swollen and vacuolated. There was evidence of vascular thrombosis with infarction of surrounding tissue. Bacterial colonies were noted within and immediately surrounding the affected blood vessels. The meninges were thickened by the infiltration of numerous heterophils. Similar infiltrates of heterophils and lymphocytes were observed in the lamina propria of the intestine. The kidneys were severely congested and haemorrhagic, with extensive interstitial nephritis.